An Entrepreneurial Approach to Operational Excellence and Welfare for Indonesia's Fishermen - Gunardi Prakosa; Eliot Simangunsong (International Research Journal of Business Studies, 2025)
This study investigates the relationship between operational excellence through entrepreneurial approaches and fishermen's welfare in East Java, Indonesia. Using quantitative analysis of data collected from 195 fishermen, the research examines how creativity, innovation, opportunity recognition, and risk-taking influence welfare outcomes. Multiple regression analysis revealed that operational excellence significantly predicts fishermen's welfare, with creativity, innovation, and risk-taking emerging as significant predictors. The findings demonstrate that fostering entrepreneurial traits among fishermen can lead to improved operational excellence and enhanced welfare outcomes. This study contributes to the literature by highlighting the importance of entrepreneurial approaches in traditional sectors and provides practical implications for policymakers and fishing industry stakeholders seeking to improve fishermen's socioeconomic conditions through operational excellence initiatives.